Antifungal activity test of nanosilver combination with lip balm cosmetic preparation - Elys Safitri; Titik Taufikurohmah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Nanosilveris is a silver-based material with nanometer particle sizes (1-100 nm) predicted to be antifungal or an alternative to preservatives in lip balm preparations that are biocompatible. The nanosilver synthesis process in this study used the bottom-up method by adding sodium citrate as a reducing agent and stabilizer. This study aimed to determine the characteristics of the results of 20 ppm nanosilver synthesis using a UV-Vis and TEM spectrophotometer and to determine the antifungal activity of nanosilver in lip balm cosmetic preparations. Variations in adding 20 ppm nanosilver into lip balm preparations are 5%, 10%, and 15%. The results of characterization using a UV-Vis spectrophotometer, namely 20 ppm nanosilver, were quite stable in storage for 2 months, and the results of characterization using TEM also showed that the formed nanosilver remained stable with a nanometer size range ranging from 11.42 nm to 43.95 nm. The antifungal activity test was carried out using the Direct Microscopic Count (DMC) method by counting directly under a microscope. Based on the data obtained, it shows that the antifungal activity of the combination of nanosilver and lip balm preparations is almost equivalent to the antifungal activity of parabens. It has produced lip balm preparations with nanosilver. This is indicated by the value of the inhibition rate (%). The inhibition of fungal growth produced by lip balm preparations with parabens is almost the same as the inhibition rate (%) produced by lip balm preparations with nanosilver. The inhibition rate of lip balm preparations with parabens was 89.11%. In comparison, the inhibition rate of lip balm preparations with a nanosilver concentration of 15% was 82.31%, so it can be concluded that nanosilver has good antifungal activity and is biocompatible so that nanosilver can be used as an alternative to paraben preservatives.